Has the development gap between the ethnic minority and majority groups narrowed in Vietnam?: Evidence from household surveys - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2018)
Using household data for rural northern Vietnam between 1993 and 2014, we find that the ethnic minority group continued to lag behind the majority group in various development indicators despite the overall improvement in living standards. Our regression and decomposition analyses show that the structural differences between the two groups are an important cause of persistent development gap. However, the nature of structural differences changed over time and no single source of structural difference explains the persistent gap. We argue that more minority‐appropriate policies are needed to lift poor minority households out of poverty further and reduce the development gap.